Paradigma prazdnika v trudah V. Ja. Proppa i M. M. Bahtina - Kaman, Eržebet (Studia mythologica Slavica, 1999)
The authoress compares two monographs "Russian agrarian feasts" (1963) by V. Propp and "Rabelais and his world"(1965) by M. Bahtin. Both books deal from different angels with analysis of the carnival held after the winter solstice, celebrating life and the awakening of nature
Keywords: ethnology; etnologija; šege; Rusija; ljudsko slovstvo; oral literature